Development of Plate Fin Heat Exchanger Using Solidwork Toward IR 4.0 - CHE SULONG, CHE ISMAIL; MAT HASSAN2, NIK NORMUNIRA; MUSTAFA, SYAZFIQ SYAZWAN (Progress in Engineering Application and Technology, 2021)
Nowadays, heat exchangers are important used in the industry no matter the small or large industry, Heat exchanger is a heat transfer system used for internal heat transfer between two or more fluids at different temperatures. The fluids in most heat exchangers are isolated by the surface of a heat transfer and are preferably not mixed. The process, electricity, oil, transportation, air conditioning, refrigeration, cryogenics, heat recovery, alternative fuels, and other industries typically uses heat exchangers. HPL Technologies are the company was facing the problem in designing the fin plate heat exchanger to provide a higher efficiency of heat exchanger for HVAC system. This section explain regarding the finding of this project from the starting point until completion the project. The flowchart diagram is essential to represent the succession of tasks to complete the work as a guideline that needs to be follow, this section also show the procedure/step to design heat exchanger using Solid Works Software, and also show the step to make simulation using Finite Element Analysis (FEA) in solidwork. In conclusion, the objective of this project successfully achieved which is list the important parameter of fin plate heat exchanger (FPHE), develop FPHE controlled by design table, and provided 3 types of diameter tube for FPHE.